The fundamental solution of Cauchy problem for a single equation of the diffusion equation with inertia - Malytska, H.P.; Burtnyak, I.V. (Carpathian Mathematical Publications, 2014)
The paper found the explicit form of the fundamental solution of Cauchy problem for the equation of Kolmogorov type that has a finite number groups of spatial variables which are degenerate parabolic.